A The Role of Islamic Education in Combating Radicalism Through Religious Moderation - Dinda Sukmayanti; Siti Soleha; Ahmad Sulhan (International Journal of Technology and Education Research, 2026)
In Indonesia, Islamic education plays a very important role in efforts to combat radicalism while promoting religious moderation. The Ministry of Religious Affairs emphasizes that religious education should be an integral part of the school curriculum, highlighting the balance between intellectual and spiritual development. This emphasis has become increasingly relevant due to the emergence of horizontal conflicts often triggered by radicalism and intolerance resulting from narrow and non-moderate interpretations of religion. Teachers and Islamic education institutions bear significant responsibility in disseminating a correct understanding of key Islamic concepts such as tolerance, jihad, and tawhid. A proper understanding of these concepts can prevent students from adopting extremist interpretations and guide them toward the values of Islam as rahmatan lil ‘alamin (a mercy to all creation). The findings indicate that inclusive character education is capable of shaping a younger generation that appreciates multicultural life and is accustomed to living in diversity with mutual respect. Madrasahs and Islamic boarding schools (pesantren) function as important Islamic educational institutions in instilling moderate values. Through comprehensive learning processes, these institutions not only provide religious knowledge but also foster students’ morality and character, enabling them to become more open-minded and tolerant. However, to effectively address the challenges of radicalism, strong synergy among educational institutions, parents, communities, and the government is essential.